Corrosion engineering towards efficient oxygen evolution electrodes with stable catalytic activity for over 6000 hours - Liu, Yipu; Liang, Xiao; Gu, Lin; Zhang, Yu; Li, Guo-Dong; Zou, Xiaoxin; Chen, Jie-Sheng (Nature communications, 2018)
Although a number of nonprecious materials can exhibit catalytic activity approaching (sometimes even outperforming) that of iridium oxide catalysts for the oxygen evolution reaction, their catalytic lifetimes rarely exceed more than several hundred hours under operating conditions. Here we develop an energy-efficient, cost-effective, scaled-up corrosion engineering method for transforming inexpensive iron substrates (e.g., iron plate and iron foam) into highly active and ultrastable electrodes for oxygen evolution reaction. This synthetic method is achieved via a desired corrosion reaction of iron substrates with oxygen in aqueous solutions containing divalent cations (e.g., nickel) at ambient temperature. This process results in the growth on iron substrates of thin film nanosheet arrays that consist of iron-containing layered double hydroxides, instead of rust. This inexpensive and simple manufacturing technique affords iron-substrate-derived electrodes possessing excellent catalytic activities and activity retention for over 6000 hours at 1000 mA cm -2 current densities. Earth-abundant water splitting materials are highly desirable for renewable fuel production, but such catalysts are rarely tested for long-term use. Here, the authors prepare active water-splitting electrocatalysts via corrosion engineering that are stable for thousands of hours.